Epistemological Foundations of Bioethics and its Implications for Policy and Global Ethics - Elias Ifeanyi E. Uzoigwe; Paul Ogbonna Chukwu (Pinisi Journal of Social Science, 2026)
This research seeks to explore the epistemic origins of bioethics and its relevance for 21st century philosophy. Bioethics, as an area of study, merges moral philosophy, medicine, law, and social sciences to solve ethical problems resulting from breakthroughs in healthcare and biotechnology. The study demonstrates how bioethical reasoning depends on the integration of realistic information, normative principles, and reflective judgment, underlining that ethical decision-making is both morally and epistemically founded. Classical ethical frameworks, including Kantian ethics, utilitarianism, and virtue ethics, provide foundational insights into moral reasoning, while contemporary approaches such as principlism, feminist bioethics, and postmodern perspectives address the complexity of modern biomedical and technological concerns. The report outlines major epistemological concerns, including the integration of scientific data with ethical reasoning, managing uncertainty, resolving epistemic heterogeneity, repairing epistemic injustice, and assessing technology interventions in healthcare. Evaluating these challenges, the study reveals that bioethics promotes philosophical inquiry by developing contemplative practice, cultural sensitivity, and practical moral reasoning. The conversation further highlights the significance of bioethics for practical philosophy globally, particularly in addressing challenges of justice, authority, and decision-making in a technologically and socially complex society. Essentially, this study argues that the epistemological foundations of bioethics give philosophers and practitioners the means to grapple with ambiguity, incorporate various viewpoints, and make morally sound choices, emphasizing the close relationship between morality, knowledge, and practical action in our contemporary world.